Fabrication and properties of oxide semiconductor nanowires - Shen, Youde (2016)
Semiconductor nanowires have been intensively studied because of their novel properties in the past two decades. Lots of interesting nanostructures have been demonstrated via the famous vapor-liquid-solid (VLS) mechanism. This bottom-up synthesis is significant for extensive applications in sensing, photonics, electronics and energy conversion. Studying nanowire growth behaviour and controlling nanowire morphology are the central theme in nanoscience and nanotechnology. Herein, we bring insights to the conventional VLS growth mechanism in the growth of lateral and kinked nanowires and advance the study of Gibbs-Thomson effect in planar nanowires growth. We report the growth of planar, vertical and randomly oriented tin-doped indium oxide (ITO) nanowires. Those differently oriented nanowires could be grown on yttria-stabilized zirconia (YSZ) substrates with an epitaxial relationship in the VLS mechanism. The growth temperature is the only parameter to be regulated. Our (scanning) transmission electron microscopy and reciprocal space mapping experiments revealed that the substrate-nanowire epitaxy had essential role in the growth of oriented in-plane and out-of-plane nanowires at the higher growth temperatures. On the contrary, the randomly oriented nanowires grew at lower growth temperature. In addition, the control of the symmetry, orientation and structure of the nanowires was also demonstrated by using (110) and (111) YSZ substrates. Based on these results, we obtained regular arrays of lateral ITO nanowires by using patterned Au catalyst nanoparticles. Furthermore, we demonstrate the direct observations of the Gibbs-Thomson effect in planar nanowires for the first time. Our systematic studies showed that the growth velocity of planar indium tin oxide (ITO) NWs conformed to Gibbs-Thomson effect and could be modulated by tin doping concentrations in spite of their rich growth directions and complex shapes. A growth model based on the surface energy was developed to explain the increasing cutoff diameter with decreasing tin doping concentration and the different cutoff diameter on different oriented substrates. We demonstrated the unprecedented growth behaviors of indium oxide (IO) nanostructures and revealed the important function of the tin dopants. At last, we report the growth of kinked single-crystalline In2O3 nanostructures consisting of nanocone base and nanowire tip connected without any twin boundaries or stacking faults. During the tailored growth, when the diameter of gold catalyst nanoparticle at the apex of the nanocone shrunk to ~100 nm as a result of the gold atom migration, the growth direction switched from [111] to either [110] or [112], depending on the growth conditions. Our results indicated that the size-dependent free energies of different oriented nanowires dictated the switching of growth directions, and the mechanism of forming such novel nanocone-nanowire kinked nanostructure may be universal for a wide range of functional materials.